2021
DOI: 10.3349/ymj.2021.62.10.885
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement versus Sutureless Aortic Valve Replacement: A Single Center Retrospective Cohort Study

Abstract: Purpose This study sought to compare clinical outcomes between transcatheter aortic valve replacement (TAVR) and sutureless aortic valve replacement (SU-AVR). Materials and Methods In total, 320 patients with symptomatic severe aortic stenosis who underwent TAVR (n=254) or SU-AVR (n=66) at Severance Cardiovascular Hospital between July 2011 and September 2019 were included for analysis. Propensity score matching and inverse probability weighted adjustment were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…After excluding duplicates and noneligible studies, ten studies [16][17][18][19][20][21][22][23][24][25] met our eligibility criteria (Figure 1). All studies were nonrandomized and observational, with two studies being prospective and four studies multicentric (Table 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding duplicates and noneligible studies, ten studies [16][17][18][19][20][21][22][23][24][25] met our eligibility criteria (Figure 1). All studies were nonrandomized and observational, with two studies being prospective and four studies multicentric (Table 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Ten studies [16][17][18][19][20][21][22][23][24][25] reported their 30-day mortality rates (Table 5 and Figure S1). We observed that the pooled risk of 30-day mortality did not favor any groups (OR: 0.69; 95% CI: 0.31-1.53; p = 0.360).…”
Section: Primary Endpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical risk was estimated using the European System for Cardiac Operative Risk evaluation (EuroSCORE II) and the Society of Thoracic Surgeons Predicted Risk of Mortality (STS-PROM) score ( 11 , 12 ). The decision to use TAVR as the treatment modality was made by a multidisciplinary heart team, as previously reported ( 13 , 14 ). The transcatheter aortic valve type was chosen at the discretion of the operators based on the anatomical characteristics of the aortic valve, aortic root, and vascular access.…”
Section: Methodsmentioning
confidence: 99%
“…Despite many advances in surgical techniques along with qualification of prosthetic valves, complications of valve replacement procedures such as infective endocarditis, dehiscence, paravalvular leak (PVL), abscess formation, aortic dissection, coronary artery occlusion, mediastinitis, brain stroke, heartbeat irregularity, and arrhythmias remains significant. [ 9 10 ] To reduce the mentioned surgical complications, several methods have been performed by heart surgeons. In the present study, the complications of AVR surgery have been compared between the two surgical techniques for AVR.…”
Section: Introductionmentioning
confidence: 99%